Process Improvement to Enhance Quality in a Large Volume Labor and Birth Unit. Issue 6 (November 2016) - Bell, Ashley M.; Bohannon, Jessica; Porthouse, Lisa; Thompson, Heather; Vago, Tony
Abstract: Background: The goal of the perinatal team at Mercy Hospital St. Louis is to provide a quality patient experience during labor and birth. After the move to a new labor and birth unit in 2013, the team recognized many of the routines and practices needed to be modified based on different demands. Methods: The Lean process was used to plan and implement required changes. This technique was chosen because it is based on feedback from clinicians, teamwork, strategizing, and immediate evaluation and implementation of common sense solutions. Through rapid improvement events, presence of leaders in the work environment, and daily huddles, team member engagement and communication were enhanced. The process allowed for team members to offer ideas, test these ideas, and evaluate results, all within a rapid time frame. For 9 months, frontline clinicians met monthly for a weeklong rapid improvement event to create better experiences for childbearing women and those who provide their care, using Lean concepts. At the end of each week, an implementation plan and metrics were developed to help ensure sustainment. The issues that were the focus of these process improvements included on-time initiation of scheduled cases such as induction of labor and cesarean birth, timely and efficient assessment and triage disposition, postanesthesia care and immediate newborn care completed within approximately 2 hours, transfer from the labor unit to the mother baby unit, and emergency transfers to the main operating room and intensive care unit. Results: On-time case initiation for labor induction and cesarean birth improved, length of stay in obstetric triage decreased, postanesthesia recovery care was reorganized to be completed within the expected 2-hour standard time frame, and emergency transfers to the main hospital operating room and intensive care units were standardized and enhanced for efficiency and safety. Participants were pleased with the process improvements and quality outcomes. Clinical Implications: Working together as a team using the Lean process, frontline clinicians identified areas that needed improvement, developed and implemented successful strategies that addressed each gap, and enhanced the quality and safety of care for a large volume perinatal service. Abstract : After a move to a new labor and birth unit, nurse leaders recognized the need to evaluate several processes and operations to enhance quality, safety, and efficiency. Elective labor induction, scheduled cesarean birth, obstetric triage, and transfer of maternity patients within the hospital are some of the aspects of care that were studied and improved by staff nurses and nursing leaders working in collaboration with other members of the perinatal team. These processes commonly present challenges in maternity units, so lessons learned may be applicable to other nurses caring for women during labor and birth.